Application of Head Elevation on Intracarnial Pressure in Stroke Patients - Kiswanto, Logi; Yamin, M.; Hidayat, Aris Teguh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of applying head elevation to intracranial pressure in stroke patients. This research method uses one data, namely a literature study. The results showed that head elevations of 0°, 15°, 30°, and 45° affected intracranial pressure in stroke patients. In conclusion, it shows that 30° more head elevation can improve the intracranial pressure problem, although the difference's value is not significant. Keywords: Head Elevation, Intracranial Pressure, Stroke